Pengaruh Kompetensi Sumber Daya Manusia dan Penerapan Sistem Informasi Akuntansi Terhadap Kualitas Laporan Keuangan di UMKM Kabupaten Sleman - Maulida Rahmawati; Muhamad Rifandi (EKOMA : Jurnal Ekonomi, Manajemen, Akuntansi, 2023)
One of the problems faced by Micro, Small, and Medium Enterprises (MSME) in Indonesia is accounting information. The inability of entrepreneurs in accounting practices is the main factor that triggers failure in developing these MSME. This research aims to discover the effect of human resource competency and the implementation of an accounting information system on the quality of financial statements of MSME in Sleman. This quantitative research was conducted through the associative method. The subjects were the MSME entrepreneurs of the fashion sector in Sleman, Yogyakarta. Using a random sampling technique, there were 100 employees of the finance department gathered from 57 MSME. Afterward, the data were obtained through a questionnaire. The results of data processing showed several points: (1) there was a positive impact in human resource competency of MSME on financial statements quality (2) there was a positive impact if accounting information system of MSME on financial statements quality (3) Human resource competency and accounting information system could give a simultaneous positive impact on the quality of financial statements.